Advanced design of hybrid energy storage system to achieve low weight for aircraft applications - Abubakar, Abdullahi (2025)
The growing demand to reduce carbon emissions poses a significant challenge for the aviation industry, particularly due to its contribution to greenhouse gas emissions, which are a major factor in climate change. The transportation sector is responsible for emitting high amount of CO_2 annually, along with other harmful pollutants, which have been linked to deaths.